(untitled) (Islas, 2022)
ABSTRACT: Introduction: The exercise of journalism in the digital space takes prominence at present so this article aims to: Propose a strategy to raise the quality of hypermedia journalism performed by graduates of the Journalism career of the Universidad Central «Marta Abreu» de Las Villas.Methods: To obtain the results were applied methods such as grounded theory and phenomenology. Results: Changes are designed in three fundamental areas: professional training, media and postgraduate training that contribute to raising the level of graduates. Conclusions: The importance of increasing the quality of hypermedia journalism in graduates leads to an interdisciplinary approach and actions.